Chemical and mineralogical changes associated with leachate production at Kriel Power Station ash dam - Bezuidenhout, Nico (Department of Geological Sciences, 2024)
ESKOM is the biggest producer of electricity in Southern Africa and generated 22mt of ash from its coal burning power stations in 1994. Of the 22 mt of ash only 5% was utilized and the rest disposed of in either landfills or ash dams. Various environmental impacts are associated with the disposal of ash including loss of usable land, dust pollution, water pollution and effects on vegetation. Current research into the environmental impact of fly ash disposal has focused on the dissolution of fly ash and the physical and chemical characteristics of unreacted fly ash particles. Few studies have investigated the chemical and mineralogical transformations that occur during the weathering of ash and little is known concerning secondary mineral formation associated with weathered ash from large ash deposits. The objective of this study was to investigate the dissolution characteristics of fly ash particles, the physical and chemical alteration of fly ash in a real weathering environment and the formation of secondary weathering products associated with ash dams. The research was based on a core section that was drilled through the ash dam of Kriel power station, precipitate samples associated with the water that is used to transport the ash to the ash dam and samples of the ash water and leachate.